ANALISIS PENGARUH KOMPETENSI TEKNISI, SARANA PRASARANA DIKLAT, DAN PELAYANAN TERHADAP CAPAIAN PROGRAM DIKLAT - Nurdin Nurdin (Sekolah Menengah Kejuruan (SMK) Pustek, 2020)
The purpose of this study was to determine the effect of technician ability, facilities and infrastructure and service toward training program achievement either partially or simultaneously. The object research carreid out to the airmen estemp of Indonesia Flight High School. Design research conducted in the preparation of this is associative quantitative that aims to determine the influence between two or more deeply variables describe or reveal a problem, situation, event or revealing fact as they are deeply and try to find a solution or solutions to problems. The results showed that technician competency, facilities and infrastructure was positive and significant effect on the achievement program train. Therefore result of determinate coefficient (R2) of 56,3% can be summed up the effect of the variable x1, x2 and x3 to variable Y where the influence are positive. It can be stated that the multiple correlation is significant. Thus the null hypothesis (H0) that states there is no effect of technician competency, training facilities and infrastructure, and services to airmen training program achievement in Indonesia flight high school is rejected, while the alternative hypothesis (Ha) are accepted